2010
DOI: 10.1029/2009gl041851
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for the estimation of thermal inertia

Abstract: [1] A simple method for estimating thermal inertia using daily amplitude of surface soil heat flux and temperature is proposed. Based on an analytical solution of the diffusion equation where the soil temperature is idealized as a sinusoidal function, the thermal inertia is expressed as a proportional coefficient in a linear equation relating the amplitudes of surface soil (ground) heat flux and temperature. Tests of the proposed method demonstrate that this simple method is potentially useful in the Earth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…Based on the NDWI , Wang et al [104] proposed using the normalized multi-band drought index ( NMDI ), which uses the band differences between the sensitivity of 1640 nm and 2130 nm for soil and vegetation, respectively, with enhanced sensitivity to drought monitoring. The successful application in detecting forest fires demonstrated that NMDI can provide a quick response to moisture changes [105,106]. NMDI=R860 nm(R1640 nmR2130 nm)R860 nm+(R1640 nmR2130 nm) where R is the reflectance.…”
Section: Sm Estimation From Optical and Thermal Remote Sensingmentioning
confidence: 99%
“…Based on the NDWI , Wang et al [104] proposed using the normalized multi-band drought index ( NMDI ), which uses the band differences between the sensitivity of 1640 nm and 2130 nm for soil and vegetation, respectively, with enhanced sensitivity to drought monitoring. The successful application in detecting forest fires demonstrated that NMDI can provide a quick response to moisture changes [105,106]. NMDI=R860 nm(R1640 nmR2130 nm)R860 nm+(R1640 nmR2130 nm) where R is the reflectance.…”
Section: Sm Estimation From Optical and Thermal Remote Sensingmentioning
confidence: 99%
“…The utility of thermal remote sensing in detecting energy and moisture fluxes at the land surface is well documented [11][12][13][14][15]. For the purpose of monitoring soil moisture content, the common scheme is to decouple the surface thermal properties from ambient temperature (daily temperature cycle) by calculating the thermal inertia (TI), which is a physical property that characterizes the surface resistance to ambient temperature change [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The diurnal variation of near-surface air temperature may be expressed in terms of a weighted time average (i.e., half-order integral) of sensible heat flux analogous to the half-order integral model of soil temperature and ground heat flux (Wang and Bras 1999;Bennett et al 2008):…”
Section: B Sensible Heat Flux Modelmentioning
confidence: 99%
“…In steps one and two, I is set at 3000 thermal inertia units (tiu; 1 tiu 5 1 J m 22 K 21 s 21/2 ) as an initial guess. In step three, the hourly temperature and sensible heat flux obtained from step two are used to estimate I as the regression coefficient between diurnal amplitudes of air temperature DT a and sensible heat flux DH according to the following equation (Wang et al 2010):…”
Section: A Proceduresmentioning
confidence: 99%
See 1 more Smart Citation